Evidence of nonsurgical treatment for polycystic liver disease - Jeong-Ju Yoo; Hye In Jo; Eun-Ae Jung; Jae Seung Lee; Sang Gyune Kim; Young Seok Kim; Beom Kyung Kim (SAGE Publishing, 2022)
Background: Polycystic liver disease (PCLD) is the most common extrarenal manifestation of polycystic kidney disease. There is an urgent need to assess the efficacy and safety of nonsurgical modalities to relieve symptoms and decrease the severity of PCLD. Herein, we aimed to evaluate the efficacy of the nonsurgical treatment of PCLD and the quality of life of affected patients. Methods: PubMed, Ovid, MEDLINE, EMBASE, and the Cochrane Library were searched for studies on the nonsurgical modalities, either medications or radiological intervention to manage PCLD. Treatment efficacy, adverse events (AEs), and patient quality of life were evaluated. Results: In total, 27 studies involving 1037 patients were selected. After nonsurgical treatment, liver volume decreased by 259 ml/m [mean change (Δ) of 6.22%] and the effect was higher in the radiological intervention group [−1617 ml/m (−15.49%)] than in the medication group [−151 ml/m (−3.78%)]. The AEs and serious AEs rates after overall nonsurgical treatment were 0.50 [95% confidence interval (CI): 0.33-0.67] and 0.04 (95% CI: 0.01-0.07), respectively. The results of the SF-36 questionnaire showed that PCLD treatment improved physical function [physical component summary score of 4.18 (95% CI: 1.54-6.83)] but did not significantly improve mental function [mental component summary score of 0.91 (95% CI: −1.20 to 3.03)]. Conclusion: Nonsurgical treatment was effective and safe for PCLD, but did not improve the quality of life in terms of mental health. Radiological intervention directly reduces hepatic cysts, and thus they should be considered for immediate symptom relief in patients with severe symptoms, whereas medication might be considered for maintenance treatment. Registration number: PROSPERO (International Prospective Register of Systematic Reviews) CRD42021279597